The Conjugate of a Difference of Functions Defined on Different Spaces - RODRIGUES, Brian (Institutional Knowledge at Singapore Management University, 1989)
Using a generalization of the chain rule of subdifferential calculus we derive expressions for the conjugate of the difference of functions defined on different spaces. As a consequence we are able to extend PSCHENICHNYI'S formula for (M - N)* such as generalized by HIRIART-URRUTY.